2014
DOI: 10.1371/journal.pcbi.1003666
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting Microarray Data with Literature-Based Knowledge to Enhance Gene Regulatory Network Inference

Abstract: Gene regulatory networks are a crucial aspect of systems biology in describing molecular mechanisms of the cell. Various computational models rely on random gene selection to infer such networks from microarray data. While incorporation of prior knowledge into data analysis has been deemed important, in practice, it has generally been limited to referencing genes in probe sets and using curated knowledge bases. We investigate the impact of augmenting microarray data with semantic relations automatically extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…Their method showed high accuracy levels for atherosclerosis. Chen et al [4] presented a method that constructs a gene-regulatory network using micro-array data and literaturebased knowledge. They first extracted gene-gene relationships from the literature and then assigned random weights to the relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Their method showed high accuracy levels for atherosclerosis. Chen et al [4] presented a method that constructs a gene-regulatory network using micro-array data and literaturebased knowledge. They first extracted gene-gene relationships from the literature and then assigned random weights to the relationships.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, some efforts in this direction have started to appear, although mostly for qualitative models [3,23,24] or with a focus on using one biological dataset combined with previous knowledge [25]. Microarrays are suitable also for quantitative integration, since they continue to provide a cost-effective platform for generating diverse quantitative data, measuring different processes and with online databases available.…”
Section: Introductionmentioning
confidence: 99%
“…The mathematical methods help in generating dynamic model for gene regulatory networks (Hecker et al, 2009). Recently, methods such as compressive sensing (Chang et al, 2014), evolutionary algorithms (Thomas and Jin, 2014) and literature-based knowledge (Chen et al, 2014) are being used for reconstruction of gene regulatory networks. Compressive sensing method takes advantage of the network's sparseness, it assume the biological networks are sparse networks which means most of the genes have interaction with small number of genes (Burda et al, 2011;Milo et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…One benefit of the reconstruction methods involving evolutionary algorithms is due to the identification of both connectivity and parameters simultaneously from a given experimental data (Thomas and Jin, 2014). Chen et al (2014) reported literature based knowledge to infer gene regulatory network.…”
Section: Introductionmentioning
confidence: 99%